Restructuring of Pakistan Journal of Ophthalmology - Moin, Muhammad (Pakistan Journal of Ophthalmology, 2012)
The primary objective of the Ophthalmic Society of Pakistan is promotion of education and science in the field of Ophthalmology. The Pakistan Journal of Ophthalmology is the principal tool through which the second objective is to be attained. To achieve this objective the PJO has to adapt and change. The cause of science in Pakistan will be served if the PJO gets recognition in national and international databases and builds the impact factor of the journal. To meet these objectives Pakistan journal of ophthalmology has been undergoing evolutionary changes for the last few years. To improve the impact factor and get accreditation the PJO needed to become an electronic Journal, recruit competent peer review members and establish standard operating procedures (SOP) for publishing. Some of the objectives have been met and